Doping control container for urine stabilization: a pilot study. Issue 5 (21st September 2016) - Tsivou, Maria; Giannadaki, Evangelia; Hooghe, Fiona; Roels, Kris; Van Gansbeke, Wim; Garribba, Flaminia; Lyris, Emmanouil; Deventer, Koen; Mazzarino, Monica; Donati, Francesco; Georgakopoulos, Dimitrios G.; Van Eenoo, Peter; et al.
Abstract : Urine collection containers used in the doping control collection procedure do not provide a protective environment for urine, against degradation by microorganisms and proteolytic enzymes. An in‐house chemical stabilization mixture was developed to tackle urine degradation problems encountered in human sport samples, in cases of microbial contamination or proteolytic activity. The mixture consists of antimicrobial substances and protease inhibitors for the simultaneous inactivation of a wide range of proteolytic enzymes. It has already been tested in lab‐scale, as part of World Anti‐Doping Agency's (WADA) funded research project, in terms of efficiency against microbial and proteolytic activity. The present work, funded also by WADA, is a follow‐up study on the improvement of chemical stabilization mixture composition, application mode and limitation of interferences, using pilot urine collection containers, spray‐coated in their internal surface with the chemical stabilization mixture. Urine in plastic stabilized collection containers have been gone through various incubation cycles to test for stabilization efficiency and analytical matrix interferences by three WADA accredited Laboratories (Athens, Ghent, and Rome). The spray‐coated chemical stabilization mixture was tested against microorganism elimination and steroid glucuronide degradation, as well as enzymatic breakdown of proteins, such as intact hCG, recombinant erythropoietin and small peptides (GHRPs, ipamorelin), induced by proteolytic enzymes. Potential analytical interferences, observed in the presence of spray‐coated chemical stabilization mixture, were recorded using routine screening procedures. The results of the current study support the application of the spray‐coated plastic urine container, in the doping control collection procedure. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Pilot sample collection containers in sports doping control were spray coated with stabilization mixture providing antimicrobial and anti‐proteolytic protection in urine samples. Pilot containers proved to be effective in terms of urine preservation for prohibited substances. No analytical interferences were recorded for small molecules and peptides analysis. The current approach opens a new era in the doping control sampling procedure.